The Impact of Binocular Vision and Tracking Intervention on Academic Performance: An In-School Vision Therapy Pilot Program. - Bush, Sara; Hinkley, Sarah; Jenerou, Alison; Damari, David; Buckingham, Robert; Geneva, Cynthia; Reger, Michael (Optometry & Visual Performance, 2019)
Background: Convergence insufficiency (CI) and saccadic deficiency (SD) are common visual conditions that can cause negative effects on a child's learning. It is postulated that with early vision therapy (VT) intervention to treat these visual conditions, associated learning difficulties and frustrations could be avoided as a child progresses through school. Methods: Twenty-nine second grade students were evaluated for a binocular vision or oculomotor disorder. Subjects diagnosed with a disorder were enrolled in an in-school VT program, grouped based on their diagnosis. Seventeen subjects completed the VT program. At the end of VT, those who completed therapy were evaluated to monitor their progress and academic performance. Results: Subjects diagnosed with CI showed a statistically significant improvement in their near point of convergence (NPC) break value (p=0.042). Subjects diagnosed with SD showed a statistically significant improvement in their Developmental Eye Movement (DEM) test adjusted horizontal score (p=0.008), DEM ratio (p=0.037), Northeastern State University College of Optometry (NSUCO) saccade testing accuracy (p=0.043), head movement (p=0.003), and body movement (p = 0.010) scores, as well as mathematics standardized testing (p=0.034) scores. Subjects who were not enrolled in VT showed a statistically significant improvement in their math standardized test scores (p=0.018). When comparing all subjects who were enrolled in VT to all subjects who were not, there was a statistically significant difference in the pre-therapy math (p=0.036) and reading (p=0.003) standardized test scores, in the post-therapy math standardized test scores (p=0.012), and in the difference between pre- and post-standardized math scores (p=0.047). Conclusion: In-school VT has the potential to create improvements in visual performance for children, especially those with SD. This type of program also has the potential to improve standardized test scores in math (especially in those with SD) and reading. Further research is needed to determine whether a longer course of VT or a program structured differently may improve results in children with CI.